Correlation between the Serum Pepsinogen I Level and the Symptom Degree in Proton Pump Inhibitor-Users Administered with a Probiotic - Muneki Igarashi; Jun Nagano; Ayumi Tsuda; Takayoshi Suzuki; Jun Koike; Tetsufumi Uchida; Masashi Matsushima; Tetsuya Mine; Yasuhiro Koga (MDPI AG, 2014)
In patients with functional upper gastrointestinal disorders such as gastroesophageal reflux disease and functional dyspepsia, the presence of symptoms is thought to occur in the absence of any organic diseases and the mechanisms behind this remain unclear. We therefore examined the relationship between stomach-related biomarker levels and symptoms. Twenty-four outpatients who had taken proton-pump inhibitors every day were enrolled in this study. The subjects consumed yogurt containing 109 colony-forming units of Lactobacillus gasseri OLL2716 (LG21) every day for three months. They underwent four clinical examinations in total. Each examination consisted of answering a questionnaire with a frequency scale for the symptoms of GERD (FSSG), and included measurements of the serum gastrin, ghrelin, and pepsinogens I and II levels. As a result, the FSSG score and the PGI value showed a decrease and an increase, respectively, after LG21 treatment when analyzed without age adjustment. A multiple regression analysis with additional adjustments for gender and age revealed a strong association between the PGI value and the FSSG symptom scores. Therefore either the PGI level itself or the factors regulating the PGI level might be involved in the etiology of these symptoms.